Exploration of α/β/γ-peptidomimetics design for BH3 helical domains. Issue 7 (5th January 2022) - Shin, Young-Hee; Yang, Hyunjun
Abstract : Helical α/β/γ-peptidomimetics in an αγααβα-hexad repeat competes out the Bak peptide from Bcl-xL with significant resistance towards proteolytic digestion. Abstract : Systematic incorporation of ring-constrained β- and γ-amino acid residues into α-helix mimetics engenders stable helical secondary structures. In this paper, functional α/β/γ-helical peptidomimetics were explored for mimicry of BH3 helical domains, Bim as a pioneering study. The Bim-based α/β/γ-peptides in an αγααβα-hexad repeat with five helical turns inhibited the interaction between Bak and Bcl-xL with excellent resistance towards proteolytic digestion. Further optimization of the α/β/γ-backbone strategy will considerably expand the utility of functional α/β/γ-peptidomimetics, in particular due to its prominent stability against proteolysis.